Association of donor hypertension and recipient renal function in living donor kidney transplantation: A single-center retrospective study - Dienemann, Thomas; Schellenberg, Jana; Heller, Katharina; Daniel, Christoph; Amann, Kerstin Ute; Hilgers, Karl Friedrich; Schiffer, Mario; Weidemann, Alexander (Clinical Transplantation, 2019)
Transplant centers now accept living donors with well-controlled hypertension. Little is known whether hypertension in living donors affects recipient's kidney function. We aimed to examine potential differences in kidneys from hypertensive donors compared to normotensive donors with respect to renal function over 36 months and histologic findings at transplantation (T0) and 12 months after transplantation (T1). Retrospective single-center analysis of 174 living donor-recipient pairs (age > 18; transplantation date 1/2008-3/2016). Hypertension in donors was defined as being on antihypertensive medication. All biopsies were assessed by the same blinded, experienced renal pathologist. Biopsies were scored for glomerulosclerosis, IFTA, and arteriosclerosis. Regression models were used to examine the relationship of donor hypertension with renal function and histologic changes. Hypertensive donors were significantly older than normotensive donors. Chronic changes such as tubular atrophy and atherosclerosis were more evident in kidneys from hypertensive donors at T0 as well as T1. Donor hypertension was independently associated with histologic changes at T0 and T1 but not with renal function over the follow period. Despite more pronounced histologic changes in kidneys from hypertensive living donors, these grafts exhibited a similar functional outcome. However, they subsequently might be at a greater risk and warrant thorough follow-up care.
CRIS-Team WoS Importer:2019-09-27